Problems in the Implementation of a Complete Systematic Land Registration Program Regarding the Emergence of Overlapping Land Certificates - Sulistyarini, Dyah Ayu (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This study aims The purpose of this study is to analyze the factors behind the overlapping in the issuance of land certificates through the complete systematic land registration program at the Semarang City Land Office, and the guarantee of legal certainty. The research methods used in this study are: the type of research used in this study is empirical legal research, the approach method used is the structural approach and Economic Analysis Of Law. The data used is primary data with qualitative descriptive data analysis. The results of the study indicate that the factors behind the overlapping in the issuance of land certificates through the complete systematic land registration program at the Semarang City Land Office in 2023 can be seen from 3 angles, namely: First, legal substance, there are weaknesses in Article 22 and Article 24 of the Regulation of the Minister of ATR/Head of BPN RI Number 6 of 2018. Article 22, there are weaknesses in terms of the strength of evidence from a written statement regarding physical control of the land area and in good faith, and witnessed by at least 2 witnesses; Article 24, in terms of the limited space for the 14-day objection period, even though it meets the principle of publicity, it can be missed by anyone who has less access to information; Second, the legal structure, that in the process of implementing the PTSL Program, PPAT is not involved as the party authorized to make deeds, so that its legal force as evidence is very weak. The involvement of the Licensed Cadastral Surveyor Service Office as a Physical Task Force in measurement and mapping can include making basic registration maps, determining land boundaries, and making land plot maps (PBT), the results are not in accordance with the standards set by the Land Office; and Third, legal culture, namely the weak legal awareness of the community regarding the importance of administrative requirements in the land registration process. The guarantee of legal certainty in the issuance of land certificates through the Complete Systematic Land Registration Program which Overlaps at the Semarang City Land Office, is realized by taking mediation steps based on the provisions of Number 30 of 1999 and the Regulation of the Minister of ATR/Head of BPN RI Number 21 of 2020.